Improved anther culture media for enhanced callus formation and plant regeneration in rice (Oryza sativa L.) - Ali, Jauhar; Nicolas, Katrina Leslie C.; Akther, Shahana; Torabi, Azerkhsh; Ebadi, Ali Akbar; Marfori-Nazarea, Corinne M.; Mahender, Anumalla (MDPI, 2021)
Anther culture technique is the most viable and efficient method of producing homozygous doubled haploid plants within a short period. However, the practical application of this technology in rice improvement is still limited by various factors that influence culture efficiency. The present study was conducted to determine the effects of two improved anther culture media, Ali-1 (A1) and Ali-2 (A2), a modified N6 medium, to enhance the callus formation and plant regeneration of japonica, indica, and hybrids of indica and japonica cross. The current study demonstrated that genotype and media had a significant impact (p < 0.001) on both callus induction frequency and green plantlet regeneration efficiency. The use of the A1 and A2 medium significantly enhanced callus induction frequency of japonica rice type, Nipponbare, and the hybrids of indica × japonica cross (CXY6, CXY24, and Y2) but not the indica rice type, NSIC Rc480. However, the A1 medium is found superior to the N6 medium as it significantly improved the green plantlet regeneration efficiency of CXY6, CXY24, and Y2 by almost 36%, 118%, and 277%, respectively. Furthermore, it substantially reduced the albino plantlet regeneration of the induced callus in two hybrids (CXY6 and Y2). Therefore, the improved anther culture medium A1 can produce doubled haploid rice plants for indica × japonica, which can be useful in different breeding programs that will enable the speedy development of rice varieties for resource-poor farmers.